Border lines - Jaumes Privat (Voix Plurielles, 2024)
Author and artist Jaumes Privat lives in Aveyron in the south of France. His first creations date back to 1968. From 1971 to 1975, he became close to Lutte occitane, a political movement against the extension of the Larzac military camp (Aveyron). Since then, he has created his own artist books, exhibited, performed, and worked with musicians. He is an important author from the south of France.